Optically controlled 2D tunnelling in GaAs delta-doped p-n junction - Vitusevich, S. A.; Forster, A.; Belyaev, A. E.; Glavin, B. A.; Indlekofer, K. M.; Luth, H.; Konakova, R. V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
A new type of an optically controlled tunnelling process in a specially designed Esaki diode is investigated. The additional peak appears due to tunnelling of 2D electrons accumulated at ground state of delta doped layers embedded nearby the p-n junction into the valence band of the p⁺-contact. It is found that the voltage position of an additional resonant peak shifts to lower bias voltage with increasing both incident light intensity and temperature. Our experimental data and theoretical simulations show that this shift is a result of an electrical field redistribution in the region of the p-n junction caused by non-equilibrium carriers generated with optic or thermal excitation.